Laser Cladding of Al 102 Powder on Al 4047 with Direct Energy Deposition - Kim, Iksu; Kim, Minsu; Kim, Hyuntae; Lee, Moon Gu; Jeon, Yongho (Metals, 2023)
Large-scale serial production industries such as automotive and aerospace have focused on reducing weight to improve fuel economy, and many parts are manufactured from various aluminum alloys. Due to the ease of recycling of aluminum alloys, research on remanufacturing has not been very active. On the other hand, laser cladding on aluminum alloys is a surface modification and repair process that deposits a thin layer on a substrate using a laser beam whose output can be easily controlled. This makes it suitable for remanufacturing processes where thin layers of damaged parts can be easily repaired, and helps to save energy. In this study, laser cladding was performed using aluminum alloy powder (Al-102) containing Si to improve the surface hardness of Al 4047 used as automotive engine parts and repair damaged parts. Several experimental studies have been conducted regarding the effect on laser power and powder flow rate. In addition, the improvement effect through the hardness analysis of the cladded layer and the change of the microstructure through the cross-section analysis of the clad part are discussed. Finally, the experimental conditions analyzed in this study suggest a suitability for the actual remanufacturing process through multi-pass cladding through overlapping.
Keywords: Al 4047; aluminum alloy; direct energy deposition; hardness; laser cladding